The maize transposable Ds1 element is alternatively spliced from exon sequences. - Wessler, S R (1991)
The null wx-ml allele contains a 409-bp Dissociation 1 (Ds1) element in exon 9 of the maize waxy (Wx) gene. In the absence of the autonomous Activator (Ac) element, the Ds1 element cannot transpose, and this allele encodes several Wx transcripts that arise following alternative splicing of Ds1 sequences from Wx pre-mRNA. Splicing involves the utilization of three 5' splice sites and three 3' splice sites. All but one of these splice sites are in Ds1 sequences near the ends of the element. The presence of 5' and 3' splice sites near the Ds1 termini and the element's small size and AT richness are features that distinguish Ds1 elements from all other known Ds elements. It is suggested that these features may enhance the ability of Ds1 to function as a mobile intron.